The Early Punishment of Accused Women: Experiences of Pretrial Detention of Mothers and Children in a Maternal-Child Unit in Chile - Rufs, Catalina; Osorio, Victoria; González, Francisca; Carvacho, Pablo (Columbia Journal of Gender and Law, 2025)
the population deprived of liberty in Latin America and the Caribbean. This situation has significantly affected women accused of drug crimes, with those accused representing a higher proportion than those convicted of this type of crime in prison. In the face of structural gender inequalities that overburden women’s care, this heightened deprivation of liberty implies significant challenges hindering motherhood. As a result, in Chile, as in other countries, infants up to the age of two are allowed to be placed in maternal and child units in prison, both for convicted and accused persons, under the pretense of safeguarding the best interests of the child and strengthening the attachment bond. Based on interviews with accused women living in a mother-child unit with their children in Chile, this Article explores the experiences of mothers and children in the context of pretrial detention. The findings reveal precarious living conditions, difficulties in meeting children’s basic needs, and an institutional bureaucracy that contributes little to the well-being of mothers and children. In contrast to convicted women, this situation is exacerbated in the context of pretrial detention. Imprisoned children are deprived of their rights and suffer deficiencies in food, health, education, and recreation. As a result, women experience unique pains of imprisonment associated with the exercise of motherhood and care, such as uncertainty about their child’s future. This Article chronicles how pretrial detention is an early sentence that punishes, above all, based on gender and class.